Copper-catalyzed aerobic radical C–C bond cleavage of N–H ketimines - Tnay, Ya Lin; Ang, Gim Yean; Chiba, Shunsuke (Beilstein Journal of Organic Chemistry, 2015)
We report herein studies on copper-catalyzed aerobic radical C–C bond cleavage of N–H ketimines. Treatment of N–H ketimines having an α-sp3 hybridized carbon under Cu-catalyzed aerobic reaction conditions resulted in a radical fragmentation with C–C bond cleavage to give the corresponding carbonitrile and carbon radical intermediate. This radical process has been applied for the construction of oxaspirocyclohexadienones as well as in the electrophilic cyanation of Grignard reagents with pivalonitrile as a CN source.
Keywords: C–C bond cleavage; copper; ketimines; molecular oxygen; radical